(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
As the global population continues to age, the need for gender-sensitive geriatric medical care becomes increasingly important. In this article, we review the current state of gender-sensitive care for older adults in outpatient settings and propose strategies for improvement. We discuss the unique healthcare needs of elderly individuals, the impact of gender on these needs, and the potential benefits of providing gender-sensitive care. We also explore existing barriers to delivering gender-sensitive care and suggest practical approaches to overcome these challenges. By promoting gender-sensitive geriatric medical care, healthcare providers can better address the diverse needs of older adults and improve overall health outcomes